The philosophy of education as problematizing and reflective in teacher education (Research, Society and Development, 2019)
This article aims to analyze the perception of graduates of the course of Letters of the State University of Maranhão, Campus Balsas, about the curricular component "Philosophy of Education" in teacher education. The conception of the relations between the thinking and the pedagogical doing in the Philosophy of Education classes can be a differential in the teacher formation. Methodologically, analytical and explanatory research was used with the aid of questionnaires. The public was selected by the random sample, especially those who worked in basic education. The analysis of quantitative and qualitative content summarized the main categories revealed in the research, namely: 1. Philosophy of Education: problematization and reflection on educational issues; 2. Critical-reflective educational thinking in the philosophical aspect; 3. The constitution of human values in the formation of the citizen. In view of this, it was found that the discipline provided the graduates with subsidies for problematizing, reflexive and critical actions on pedagogical issues in a radical, rigorous and joint manner, according to the precepts proposed by Saviani.